2001
DOI: 10.1136/gut.49.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Arginine induced acute pancreatitis alters the actin cytoskeleton and increases heat shock protein expression in rat pancreatic acinar cells

Abstract: Arginine induced acute pancreatitis was evaluated as a novel and distinct form of experimental pancreatitis with particular attention to the actin cytoskeleton and expression of heat shock or stress proteins. Arginine induced a dose related necrotising pancreatitis in rats, as shown by histological evaluation, and an increase in serum amylase. Severe pancreatitis induced by 4.5 g/kg arginine was accompanied by dramatic changes in the actin cytoskeleton, as visualised with rhodamine phallodin. Intermediate fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 43 publications
7
63
0
2
Order By: Relevance
“…These findings were in agreement with the results of previous studies which reported these histo-pathological changes after 1 day of induction of AP [19,22,44]. According to Nevalainen and Aho [31], oedema is the most common denominator of AP induced by any method, and reflects inflammatory mechanisms.…”
Section: Discussionsupporting
confidence: 83%
“…These findings were in agreement with the results of previous studies which reported these histo-pathological changes after 1 day of induction of AP [19,22,44]. According to Nevalainen and Aho [31], oedema is the most common denominator of AP induced by any method, and reflects inflammatory mechanisms.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, a more pronounced induction of selective HSPs can protect against acute pancreatitis, depending on the model of acute pancreatitis used (32)(33)(34). In this context, HSP27 and HSP70 have been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the rat model of L-arginine- induced pancreatitis, cytoskeletal changes (27), the involvement of oxygen free radicals, NO, and inflammatory mediators (9) have all been suggested to play roles in the induction of pancreatitis. These potential mediators of L-arginine-induced pancreatitis have only been studied at later time points, thereby making it difficult to link these mediators with the initial events.…”
Section: Discussionmentioning
confidence: 99%